Solar cycle variations in the ionosphere of Mars as seen by multiple Mars Express data sets. Issue 3 (8th March 2016) - Sánchez‐Cano, B.; Lester, M.; Witasse, O.; Milan, S. E.; Hall, B. E. S.; Cartacci, M.; Peter, K.; Morgan, D. D.; Blelly, P.‐L.; Radicella, S.; Cicchetti, A.; Noschese, R.; et al.
Abstract: The response of the Martian ionosphere to solar activity is analyzed by taking into account variations in a range of parameters during four phases of the solar cycle throughout 2005–2012. Multiple Mars Express data sets have been used (such as Mars Advanced Radar for Subsurface and Ionospheric Sounding (MARSIS) in Active Ionospheric Sounding, MARSIS subsurface, and MaRS Radio Science), which currently cover more than 10 years of solar activity. The topside of the main ionospheric layer behavior is empirically modeled through the neutral scale height parameter, which describes the density distribution in altitude, and can be used as a dynamic monitor of the solar wind‐Martian plasma interaction, as well as of the medium's temperature. The main peak, the total electron content, and the relationship between the solar wind dynamic pressure and the maximum thermal pressure of the ionosphere with the solar cycle are assessed. We conclude that the neutral scale height was different in each phase of the solar cycle, having a large variation with solar zenith angle during the moderate‐ascending and high phases, while there is almost no variation during the moderate‐descending and low phases. Between end‐2007 and end‐2009, an almost permanent absence of secondary layer resulted because of the low level of solar X‐rays. Also, the ionosphere was more likely to be found in a more continuously magnetized state. The induced magnetic field from the solar wind, even if weak, could be strong enough to penetrate more than at other solar cycle phases. Key Points: Global ionosphere of Mars response to the solar cycle is investigated with multiple data sets Empirical modeling of the neutral scale height with solar cycle Temperature and pressure balance analysis with solar cycle